HUBUNGAN ANTARA INTENSITAS QUALITY TIME IBU DAN ANAK DENGAN ASERTIVITAS REMAJA DI KECAMATAN PUPUAN, KABUPATEN TABANAN - Aryaningrat, Putu Sintha Dewi; Marheni, Adijanti (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2014)
Adolescence is part in life where human change from childhood into adult (Olds, 2009). In their daily life, adolescents spend their more time with their peers (Papalia et al, 2008). An adolescent with working parent, especially adolescents in Pupuan that majorly have parents who work as a farmer, exactly have a lower intensity of time with their parent. The lower time that adolescents spend with their mother, will make a negative effects to adolescent’s cognitive development (Boca, 2012). Mother who work, will influence there adolescent. So, the researcher would like to know are there any significant relationship between the intensity of quality time among the mother and child with the adolescence assertiveness? This research used quantitative method with simple linear regression for data analysis. Researcher collected data by 2 questionnaires (intensity of quality time scale and assertiveness scale) with the reliability of 0,897 and 0,900 from 240 adolescents that take by stratified random sampling with the criterions such as adolescents with age range between 13-15 years old, live in Pupuan, and have a mother who works as farmer. This research found that there is a relationship between the intensity of quality time among the mother and child with the adolescence assertiveness with the correlation’s coefisien 0,395. There are 15,6% assertiveness is influence by the intensity of quality time among mother and child and 84,4% is influence by the other factors. For the deepen explanation, I used adolescence’s socioemotional theories from Papalia (2008). Key words: Quality time intensity, Assertiveness, Adolescence